Application of a compact trickle-bed bioreactor to the biodegradation of pollutants from the ventillation air in a copper-ore mine. (15th January 2015) - Kasperczyk, Damian; Urbaniec, Krzysztof
Abstract: Selected results are presented of an on-going project conducted by Ekoinwentyka Ltd. with the aim to design, test and apply a compact trickle-bed bioreactor – operated in a biofiltration system with circulating salt solution – to the biodegradation of VOCs, mercaptans and H2 S contained in the ventillation air in a copper-ore mine at a depth of 1000 m underground. The experiments were performed using a 48 dm 3 semi-industrial scale bioreactor in which gas and liquid phases flowed co-currently in downward direction through a bed made of polyethylene rings. The bioreactor was inoculated with a co-culture of microorganisms including bacterial strains found in the cooper-ore mine and adopted to chosen pollutants. In the laboratory tests, biodegradation of 4-components VOC mixture (acetone, styrene, benzene, vinyl acetate) and 8-component pollutant mixture (VOCs + xylene, H2 S, dimethyl sulfide, dimethyl disulfide) was studied. In the gas-flowrate range 2.0 – 15.0 m 3 /h and at a specific pollutant load up to 40 g/(m 3 h), values of the efficiency of pollutant removal above 80% were measured for all mixture components except benzene which caused bioreactor poisoning at a specific load above 5 g/(m 3 h). Possible consequences of a fatal pollutant overload and the time required for regenerating the microorganisms and returning to stable process conditions were also investigated. In the copper-ore mine, it was found that pollutant concentration in the ventillation air was normally low not exceeding values attained during laboratory tests but temporary bursts of very high H2 S concentration were also detected. An increase in H2 S concentration to 1000 ppmv lasting for 1 h caused bioreactor poisoning but after H2 S concentration returned to normal, stable process conditions were restored within 45 min. On the basis of experiments carried out both in the laboratory and copper-ore mine, acceptable values of parameters of the biodegradation process were determined. Despite harsh working conditions that are characteristic of the copper-ore mine 1000 m deep, the experimental set-up has been working reliably for several months and a high efficiency of pollutant removal has been achieved. Highlights: Biodegradation of Volatile organic compounds, mercaptans and H2 S contained in air. Compact trickle-bed bioreactor inoculated with a co-culture of microorganisms. Laboratory tests and operation in a copper-ore mine at a depth of 1000 m underground. Several months of reliable operation with a high efficiency of pollutant removal.